(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Humanism puts human interest and the mind of man paramount, rejecting the supernatural, belief in a God. Humanism lays much stress on devotion to human welfare. It is man centred philosophy. The word ‘Humanism’ is an pious as the spirit of the earth, the all embracing identity to give shelter to all living and non living things into her very heart. It is the spiritual core idea of the immortal literatureof india, the Upanishads many more thousands years ago created by great sages for human welfare. Vivekananda’s humanism may be regarded as spiritualistic humanism or Humanistic Advaitaj- which regards man as God, criticizes social, economic and religious evil of society and advocates for faith, fearlessness and strength in the individual. In the words of Swami Vivekananda, “ Man is the highest being that exists, and this is the greatest world. We can have no conception of God higher than man, so our god is man, and man is God. When we rise and go beyond and find something higher, we have to jamp out of the mind, out of the body and the imagination and leave this world; when we rise to be the absolute, we are no longer in this world. Man is the apex of the only world we can ever know. All we know of animals is only by analogy, we judge them by what we do and feel ourselves.”